Faith and Perseverance: Revd Dr Marie Isaacs (1936–2016) - Higgin, Amanda (Baptist quarterly, 2025)
Marie Isaacs was the first woman ordained in the UK Baptist Church after a significant gap, and was also exceptional in pursuing a bi-vocational ministry that included both local church ministry and academic research. Her academic publications, especially concerning the Letter to the Hebrews, are valuable contributions and suggest that this oft-ignored text is worthy of greater attention. Her life was exceptional but undramatic; she emerged with the support of her contemporaries at a time when other women were also establishing their places in both the church and the academy. Nevertheless, her persistent determination in her unique calling is exemplary.